The professional development of English language teachers in Colombia: a review of the literature - Buendía, Ximena Paola; Macías, Diego Fernando (Colombian Applied Linguistics Journal, 2019)
This article offers a review of 25 empirical studies to identify the areas and findings of professional development initiatives for in-service English teachers in Colombia. The reviewed studies suggest that language teacher professional development has focused on six major areas: language proficiency, research skills and reflective practice, teachers’ beliefs and identities, an integrated approach to teacher professional development, pedagogical skills and teaching approaches, and emerging technologies. Results suggest that there is a need to move from traditional masterapprentice, content-oriented, teacher-centered models of professional development towards initiatives that allow teachers to critically analyze their particular context and needs, and devise their own local alternatives so that they can become more active agents of their own process of change. Issues that constitute possible alternatives for future research in the professional development of English language teachers are discussed.